Analysis of Implementation Evaluation of the Tuberculosis Program at the Tambusai Health Center, Rokan Hulu Regency: Analisis Evaluasi Pelaksanaan Pada Program Tuberkulosis Di Puskesmas Tambusai Kabupaten Rokan Hulu - Guzlan Hijrul Febrizal; Dami Yanthi; Welly Sando; Reno Renaldi (Badnur Medisa Group, 2022)
Pulmonary Tuberculosis is a direct infectious disease caused by Tuberculosis Germs (Mycobacterium Tuberculosis). These bacteria generally attack the lungs, such as lymph nodes, skin, digestive tract (intestines), the lining of the brain, and so on. Tambusai Public Health Center is the lowest suspected pulmonary tuberculosis finding, where data on pulmonary tuberculosis suspects found in 2019 was 215 (21.2%) cases, in 2020 there were 198 (20%) cases, while in 2021 it was 140 (16%). The purpose of this study is to know the analysis of the implementation evaluation of the tuberculosis program at the Tambusai public health center, Rokan Hulu Regency in 2022. This type of research is a case study with a qualitative method. The research subjects were the head of the public health center, the person in charge of the pulmonary tuberculosis program at the puskesmas, doctors, nurses, and laboratory analysts. Research Time April-June 2022. Data collection was carried out by in-depth interviews, document searches and observations. The results showed that the determination of human resources was not in accordance with education in the tuberculosis control program, funding from the Provincial Office Health Operational Assistance and funds for standardized treatment of tuberculosis patients were borne by the district budget, for tuberculosis diagnosis in anamnesis by a trained doctor, for Supervision of taking drugs patient is supervised by the local midwife, while the recording and reporting of monitoring and evaluation are recorded by all those responsible for the tuberculosis program. It is recommended that the health center should look for human resources in accordance with the field and education of the pulmonary tuberculosis program, and for the diagnosis of tuberculosis patients, a separate room is given for treatment, so as not to be directly exposed to other patients, while for supervision of taking drugs the team of health workers should also review patients who have been diagnosed with tuberculosis. monitoring period for taking tuberculosis drugs regularly.